Relational Work in Peer Advice in a Chinese Corporate Online Discussion Forum (Sinología hispánica. China Studies Review, 2020)
Former studies on advice has been focused on health and educational settings eitheronline or offline, where the advice-giver usually enjoys an advantageous power relationship with theadvice-seeker. Studies of advice in Chinese discourse are no exception. Given the insufficiency ofstudies on advice given by peers of equity power relations in Chinese discourse and the necessity toinvestigate into relational aspects, this study explores peer advice given by coworkers in a Chinesecorporate online discussion forum, analyzing the advising strategies and the relational work involved.Analysis of data shows that Chinese make use of direct advising strategies more often than eitherconventionally or non-conventionally indirect strategies. Further examination of peer advice textsindicates that people are doing various types of relational work in giving advice to others online: mockcloseness, impoliteness, solidarity and non-politeness. This study may, hopefully, help to deepen ourunderstanding of advice-giving and relational work in Chinese discourse, especially in online discourse.